Contribution of Ultra-processed Food to the Daily Food Intake of HIV-positive and HIV-Negative Women during Pregnancy - Agostini, Clarissa de Oliveira; Zoche, Ester; Corrêa, Rafaela da Silveira; Chaves, Eunice Beatriz Martin; Corleta, Helena von Eye; Bosa, Vera Lúcia (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2019)
Objective To assess the daily dietary intake and energy contribution of ultra-processed foods among women who are positive and negative for the human immunodeficiency virus (HIV) during pregnancy.Methods This case–control study included 77 HIV-positive and 79 HIV-negative puerperal women between 2015 and 2016. The socioeconomic and maternal demographic data were assessed, and a food frequency questionnaire (FFQ) adapted for pregnant women was applied. The Fisher exact test and the Mann-Whitney test were applied to detect differences between the groups. Linear regression was used to assess the associations between the intake of ultra-processed food and energy, macro- and micronutrients, with values of p < 0.05 considered significant.Results The HIV-positive group was older (p < 0.001) and had lower income (p = 0.016) and level of schooling (p < 0.001) than the HIV-negative group. Both groups presented similar average food intake: 4,082.99 Kcal/day and 4,369.24 Kcal/day for the HIV-positive and HIV-negative women respectively (p = 0.258).The HIV-positive group consumed less protein (p = 0.048), carbohydrates (p = 0.028) and calcium (p = 0.001), and more total fats (p = 0.003). Ultra-processed foods accounted for 39.80% and 40.10% of the HIV-positive and HIV-negative groups' caloric intake respectively (p = 0.893). The intake of these foods was associated with a higher consumption of carbohydrates (p < 0.001), trans fat (p = 0.013) and sodium (p < 0.001), as well as lower protein (p < 0.001) and fiber intake (p = 0.022).Conclusion These findings demonstrate that the energy consumption and ultra-processed food intake were similar in both groups, which reinforces the trend toward a high intake of ultra-processed food in the general population. The intake of ultra-processed food was positively associated with the consumption of carbohydrates, trans fat and sodium, and negatively associated with the consumption of protein and fiber.
Keywords: HIV; pregnancy; micronutrients